2012
DOI: 10.1016/j.energy.2012.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models for the oxy-fuel combustion of coal and coal/biomass blend chars obtained in N2 and CO2 atmospheres

Abstract: The thermal reactivity and kinetics of five coal chars, a biomass char, and two coal/biomass char blends in an oxy-fuel combustion atmosphere (30%O 2 -70%CO 2 )were studied using the non-isothermal thermogravimetric method at three heating rates.Fuel chars were obtained by devolatilization in an entrained flow reactor at 1273 K under N 2 and CO 2 atmospheres.Three nth-order representative gas-solid models -the volumetric model (VM), the grain model (GM) and the random pore model (RPM) -were employed to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…[20] resulted in no significant difference in reactivity. Gil et al [17,21] also performed TGA experiments and observed no or just a slightly higher reactivity of the N 2 -chars. Rathnam et al [11] obtained partially similar results comparing burn-out degree of the chars in different oxygencontaining N 2 /CO 2 atmospheres at twice the residence times: two of the four examined samples showed a similar burn-out in both atmospheres, while in CO 2 -atmospheres the burn-out degree was higher for the other two coals.…”
Section: Introductionmentioning
confidence: 94%
“…[20] resulted in no significant difference in reactivity. Gil et al [17,21] also performed TGA experiments and observed no or just a slightly higher reactivity of the N 2 -chars. Rathnam et al [11] obtained partially similar results comparing burn-out degree of the chars in different oxygencontaining N 2 /CO 2 atmospheres at twice the residence times: two of the four examined samples showed a similar burn-out in both atmospheres, while in CO 2 -atmospheres the burn-out degree was higher for the other two coals.…”
Section: Introductionmentioning
confidence: 94%
“…Larger CO concentrations, formed partly due to incomplete combustion of the volatiles, and partly driven from char CO 2 gasification reactions, would also contribute to the worsening of the burning properties of the coal, by forming a persistent cloud around the particle, thereby preventing the access of oxygen to the surface of the particle [17].…”
Section: Effect Of the Diluent Background Gases (N 2 And Co 2 ) And Omentioning
confidence: 99%
“…These coal particles ignited and burned heterogeneously by direct attack of oxygen on their surfaces. Due to the known low reactivity of the anthracite AC particles [17], their ignition was delayed. The color of the particles changed from dark (black) to bright (nearly-white) as their surfaces became incandescent; this change occurred gradually over a few milliseconds.…”
Section: High-speed Cinematography Stillsmentioning
confidence: 99%
“…RPM, URCM and VM models have been used to study the coal char gasification, and a series of achievements have been reported [2][3][4][5][13][14][15][16][17]22,24]. In this paper, a new mathematical treatment of calculation kinetic parameters has been established to reduce the error caused by dealing with experimental data.…”
Section: Analysis Of Calculation Methodsmentioning
confidence: 99%
“…In order to evaluate accuracy of different models, the deviation caused by different models is calculated by Eq. (14) [22].…”
Section: Samplementioning
confidence: 98%